The Red Queen in a potato field: integrated pest management versus chemical dependency in Colorado potato beetle control. Issue 3 (6th June 2014) - Alyokhin, Andrei; Mota‐Sanchez, David; Baker, Mitchell; Snyder, William E; Menasha, Sandra; Whalon, Mark; Dively, Galen; Moarsi, Wassem F
Abstract Originally designed to reconcile insecticide applications with biological control, the concept of integrated pest management (IPM) developed into the systems‐based judicious and coordinated use of multiple control techniques aimed at reducing pest damage to economically tolerable levels. Chemical control, with scheduled treatments, was the starting point for most management systems in the 1950s. Although chemical control is philosophically compatible with IPM practices as a whole, reduction in pesticide use has been historically one of the main goals of IPM practitioners. In the absence of IPM, excessive reliance on pesticides has led to repeated control failures due to the evolution of resistance by pest populations. This creates the need for constant replacement of failed chemicals with new compounds, known as the 'insecticide treadmill'. In evolutionary biology, a similar phenomenon is known as the Red Queen principle – continuing change is needed for a population to persevere because its competitors undergo constant evolutionary adaptation. The Colorado potato beetle, Leptinotarsa decemlineata (Say), is an insect defoliator of potatoes that is notorious for its ability to develop insecticide resistance. In the present article, a review is given of four case studies from across the United States to demonstrate the importance of using IPM for sustainable management of a highly adaptable insect pest. Excessive reliance on often indiscriminate insecticide applications and inadequate use of alternative control methods, such as crop rotation, appear to expedite evolution of insecticide resistance in its populations. Resistance to IPM would involve synchronized adaptations to multiple unfavorable factors, requiring statistically unlikely genetic changes. Therefore, integrating different techniques is likely to reduce the need for constant replacement of failed chemicals with new ones. © 2014 Society of Chemical Industry